Evaluasi Pendidikan Karakter Madrasah Aliyah dan Usulan Kebijakan Pembangunan Pendidikan Karaketr Berbasis Kolaborasi Masyarakat - Priyono, Eko (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
Cases of violence, brawls between students and moral degradation are caused by character education failure, due to inappropriate learning process, not emphasizing tasks and development of adolescents and personality structure model, the lack of parents’ role and society and stakeholders. The purpose of this study is to conduct a critical analysis about character education evaluation in Islamic high schools so that it can reduce the number of brawls, violence between students and moral degradation of adolescents; and to propose a policy for developing character education based on community collaboration. This study was conducted using a qualitative approach. The data used are primary and secondary data. Results: 1) the implementation of character education in Islamic high schools in the Special Region of Jakarta cannot be used as a solution to overcome the problems of violence, brawls between students and moral degradation; 2) The weaknesses of character education implementation are analyzed using the Wisconsin version of the logic model to obtain six alternative policies; 3) the sixth alternative policy is chosen as a policy, namely the development of character education with community collaboration so that it can increase community awareness to overcome social problems involving students. Conclusion: the development of character education requires collaboration with parents, the community and stakeholders to apply these values ​​to real conditions and solve social problems in the community.